Diagnostic utility of plasma translocator protein 18 kDa (TSPO) in sepsis: A case-control study - Hattori, Miyuki; Kikutani, Kazuya; Hosokawa, Koji; Kyo, Michihito; Nishikimi, Mitsuaki; Ota, Kohei; Ohshimo, Shinichiro; Aizawa, Hidenori; Shime, Nobuaki (Medicine (Baltimore), 2024)
Translocator protein 18 kDa (TSPO) is a mitochondrial membrane protein that is involved in inflammation, oxidative stress, and steroidogenesis. TSPO may be a marker of inflammatory responses in the brain and other organs, but there have been few studies of the potential clinical significance of measuring the circulating TSPO concentration, especially in patients with sepsis. In this study, we compared the circulating TSPO concentrations of patients with sepsis and healthy controls to investigate the utility of plasma TSPO for the diagnosis of sepsis. Patients with sepsis admitted to the intensive care unit of Hiroshima University Hospital between January 2020 and April 2024 were enrolled. Plasma samples were collected from patients within 24 hours of admission and also from healthy volunteers, and their plasma TSPO concentrations were compared. Receiver operating characteristic analysis was used to evaluate the usefulness of plasma TSPO concentration for the diagnosis of sepsis. We also investigated the relationships of TSPO concentration with the severity of sepsis, complications, and prognosis of the patients. Eighty subjects (52 patients and 28 controls) were included in this study. The plasma TSPO concentrations of the patients with sepsis were significantly lower than those of the healthy controls (0.094 vs 0.25 ng/mL, P < .001), and receiver operating characteristic analysis generated an area under the curve of 0.81 (95% confidence interval: 0.72-0.91). In patients with sepsis, the TSPO concentration was not associated with the severity of sepsis, complications, or prognosis. Plasma TSPO may be a useful biomarker for the diagnosis of sepsis.